Improving the Public’s Health through Partnerships - Kimberly McFarland DDS, MHSA (2000)
Aloha! Improving the PublicÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s Health Through Partnerships, AAPHDÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s 62nd annual meeting in Honolulu, Hawaii, was truly a delight. This yearÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s meeting, October 4-8, included two days of premeeting training entitled ÃƒÂ¢Ã¢â€šÂ¬Ã‚ÂWriting for Publication,ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â in addition to the ABDPH and our annual meeting